Mental toughness among elite athletes in Iceland : comparing athletes' mental toughness in individual and team sports - Dagmar Diljá Margeirsdóttir 2000- (2024)
The psychological aspects of athletes' health have become more prevalent in the last two decades, particularly emphasising mental toughness. Recognising mental toughness as a critical psychological resource and the numerous attributes constituting this complex concept. This study explores the construct of mental toughness among elite athletes in Iceland, focusing on whether there is a difference between athletes participating in individual or team sports. While acknowledging that mental toughness is inherent, recent research indicates that mental toughness may be established through environmental factors and experiential learning. This research used the Mental Toughness Index (MTI) to assess mental toughness levels among a sample of elite athletes in Iceland. To evaluate the relationship between age and sport type and variation in mental toughness, a functional analysis of variance (FANOVA) was used. Despite the prevailing idea that individual sports demand more mental toughness, the findings reveal that the relationship is complex and not significantly influenced by age or type of sport. The results advance our knowledge of mental toughness. However, mental toughness is associated with sports achievement but is not a reliable predictor of success. It must be taken into account in the larger context. Keywords: Mental toughness, athletic performance, psychological attributes, individual sports, team sports, Icelandic athletes. Sálfræðilegir þættir í heilsu íþróttamanna hafa orðið algengari á síðustu tveimur áratugum og hefur áhersla á andlegan styrk færst í aukana. Viðurkenning hefur orðið á andlegum styrk sem mikilvægu sálfræðilegu úrræði og fjölmargair eiginleikar sem mynda þetta flókna hugtak. Í þessari rannsókn er hugtakið andlegur styrkur skoðað meðal afreksíþróttafólks á Íslandi með áherslu á hvort að munur sé á milli íþróttafólks sem stundar einstaklings- eða hópíþróttir. Þó viðurkennt sé að andlegur styrkur sé meðfæddur benda nýlegar rannsóknir til þess að andlegur styrkur geti mótast vegna ...